Soil Carbon and Structural Quality in Crop Rotations under No-tillage System - Lutécia Beatriz dos Santos Canalli; Josiane Bürkner dos Santos; Dácio Antônio Benassi; André Luiz Oliveira de Francisco; Caetano Benassi; Adriane Novakowski de Aguiar; Elielson Cordeiro; Renan Stanislavski Mendes (Brazilian Archives of Biology and Technology, 2020)
Abstract The no-tillage system associated with crops rotation affects the dynamics of soil organic matter, influencing the formation, reorganization and stabilization of aggregates and the carbon content (C) into soil aggregates. The aim of this study was to evaluate the effect of crop rotations under no-tillage system on C content and soil aggregation. The experiment was conducted at the Paraná Agronomic Institute in Ponta Grossa, PR, Brazil. The treatments consisted of six crop rotations, in a 3-year cycle, arranged in a randomized block design with four replications. Soil samples were collected at layers of 0-5, 5-10 and 10-20 cm. The aggregate classification was determined by the wet sieving methodology, and the Weighted Mean Diameter (WMD), Geometric Mean Diameter (GMD) and Aggregate Stability Index (ASI) were calculated. The C content in the aggregates was determined by wet oxidation. The results were submitted to analysis of variance and Tukey test at 5% probability. There was no difference among crop rotations for aggregate classes and aggregation indexes, but were higher in surface, decreasing in depth. The carbon content in the aggregates did not differ among crop rotations, but presented stratification in the soil profile, decreasing in depth. The cycle of three years with crop rotation was insufficient to express possible changes in soil C content and aggregation.